Anakinra for corticosteroid-dependent and colchicine-resistant pericarditis: The IRAP (International Registry of Anakinra for Pericarditis) study. (29th August 2020) - Imazio, Massimo; Andreis, Alessandro; De Ferrari, Gaetano Maria; Cremer, Paul C; Mardigyan, Vartan; Maestroni, Silvia; Luis, Sushil Allen; Lopalco, Giuseppe; Emmi, Giacomo; Lotan, Dor; Marcolongo, Renzo; Lazaros, George; et al.
Abstract: Aims: Novel therapies are needed for recurrent pericarditis, particularly when corticosteroid dependent and colchicine resistant. Based on limited data, interleukin-1 blockade with anakinra may be beneficial. The aim of this multicentre registry was to evaluate the broader effectiveness and safety of anakinra in a 'real world' population. Methods and results: This registry enrolled consecutive patients with recurrent pericarditis who were corticosteroid dependent and colchicine resistant and treated with anakinra. The primary outcome was the pericarditis recurrence rate after treatment. Secondary outcomes included emergency department visits, hospitalisations, corticosteroid use and adverse events. Among 224 patients (46 ± 14 years old, 63% women, 75% idiopathic), the median duration of disease was 17 months (interquartile range 9–33). Most patients had elevated C-reactive protein (91%) and pericardial effusion (88%). After a median treatment of 6 months (3–12), pericarditis recurrences were reduced six-fold (2.33–0.39 per patient per year), emergency department admissions were reduced 11-fold (1.08–0.10 per patient per year), hospitalisations were reduced seven-fold (0.99–0.13 per patient per year). Corticosteroid use was decreased by anakinra (respectively from 80% to 27%; P < 0.001). No serious adverse events occurred; adverse events consisted mostly of transient skin reactions (38%) at the injection site. Adverse events led to discontinuation in 3%. A full-dose treatment duration of over 3 months followed by a tapering period of over 3 months were the therapeutic schemes associated with a lower risk of recurrence. Conclusion: In patients with recurrent pericarditis, anakinra appears efficacious and safe in reducing recurrences, emergency department admissions and hospitalisations.